Development of a Modification Problem-Based Learning (M-PBL) Strategy to Stimulate Chemistry Education Students’ Metacognitive Ability - Jusniar Jusniar; Muh. Yunus; Hardin Hardin; Syamsidah Syamsidah (Universitas Negeri Malang, 2022)
This study aims to: 1) describe the stages of developing the M-PBL Strategy with the ADDIE pattern (Analyze, Design, Develop, Implementation, and Evaluate). 2) Testing the validity and practicality of the M-PBL strategy. The research subjects were three experts, two Basic Chemistry lecturers, and 35 students of the Chemistry Education Study Program, FMIPA UNM even semester of the 2020/2021 academic year. The instruments used are: 1) M-PBL Strategy Design validation sheet and its tools (Lesson Plan, Worksheet, and ability assessment; 2) lecturer and student perception questionnaires and observation sheets on the implementation of M-PBL Strategy to test the practicality of the product. The results of testing the validity of the development product (M-PBL Strategy Design and its tools), it was found that all products were in the very high category. Testing the practicality of the M-PBL strategy based on the perceptions of two lecturers was 100% giving a positive response, while the student's perception was 94.6% giving a positive response. The implementation of the stages of the M-PBL strategy is carried out as a whole with high category student activities. Thus, the Development Product is declared feasible and acceptable from the aspect of validity and practicality.